Evaluation of residual carious dentin detection methods after cavity preparation: a randomized clinical trial - Hadiza Mohammed Abba; Paul Ikhodaro Idon; Christopher Ikeokwu Udoye; Oluwafeyisayo Francis Ikusika (BMC, 2024)
Abstract Background The treatment of caries in dentine poses the challenge of balancing adequate caries removal to prevent residual caries and excessive sound dentine removal. No diagnostic tool is available to define the caries removal limit clinically. This study aimed to determine the efficiency of visual-tactile, caries detector dye (CDD), and laser fluorescence (LF) device methods for diagnosing residual caries after cavity preparation. Method The study was conducted as a three-arm, double-blinded, parallel-group randomized trial at the Restorative Dentistryclinics of a teaching hospital in northeastern Nigeria. Individualized carious lesions in dentine were randomly allocated to three groups of residual caries diagnosis methods, A (visual-tactile), B (CDD), and C (LF). All carious lesions had caries excavation and cavity preparation using the visual-tactile method. Main outcome measures were based on the assessment of residual caries of prepared cavities in groups B and C with CDD and LF (DIAGNOdent Pen) respectively, and bacterial culture growth of dentine samples collected from all (A, B, and C) the preparedcavities. Design Three-arm, double-blinded, parallel group randomized trial. A centralized randomization, into three groups A, B, and C, used opaque envelopes containing names of diagnostic methods allocated to teeth in the trail. Setting Restorative Dentistry clinics of a teaching hospital in northeastern Nigeria. Participants Ninety patients with dental caries in dentine. All 90 patients met the requirements for the study. Intervention Carious lesions were excavated, and cavity preparation was performed via the visual-tactile method. Prepared cavities in groups B and C were assessed for residual caries with CDD and LF (DIAGNOdent Pen), respectively, by a blinded independent investigator. Dentine samples were obtained from all the prepared cavities (A, B, and C) and subjected to bacterial culture. Teeth were restored and follow-up was not required. Main outcome measures The presence or absence of residual caries staining by CDD and fluorescence by DIAGNOdent in prepared cavities of groups B and C, respectively; the presence or absence of bacterial culture growth for all three groups. Results Ninety participants (mean age 31.6 ± 7.480), each with one tooth with a deep carious lesion were randomized. The visual-tactile method had a specificity of 100%, CDD had 100% sensitivity and 92.9% specificity, and DIAGNOdent had 100% sensitivity and 100% specificity when measured against bacterial cultures. The positive predictive value for CDD (50%) was half that for DIAGNOdent (100%). The negative predictive value was the lowest (90%) for the visual-tactile method. The accuracy was highest (100%) for DIAGNOdent. There was perfect agreement between the DIAGNOdent and bacteriological tests (kappa = 1.00), whereas the CDD had an above-random level of agreement (kappa = 0.63). Conclusions All three residual caries evaluation methods were efficient, independently, in detecting residual caries in prepared cavities. DIAGNOdent was the most specific of the tested modalities and had the highest agreement with the bacteriological confirmatory test. Trial registration PanAfrican Clinical Trial Registry (PACTR202309545839091), registered on 1st September 2023.